Defining Mobile Tech Posture: Prevalence and Position Among Millennials - Nathan Short; Michelle Mays; Alex Cool; Ariana Delay; Ali Lannom (Scholarworks @ WMU, 2020)
Background: Mobile technologies have revolutionized daily life, significantly impacting ADLs and IADLs, as well as use of the hand and upper extremity. The primary objectives of this study are to (a) provide a formal goniometric description of mobile tech posture and (b) examine the prevalence of this sub-optimal posture among a group of graduate students. Method: This study used a cross-sectional study design. Comprehensive goniometric measurements of the neck and upper extremity were taken with participants (N = 46) using their mobile devices while texting or using the Internet. Handheld usage data from the iPhone Screen Time feature (iOS 12) was collected from a sample of healthy young adults. Results: The participants spent an average of 143 min per day using mobile technology. Comprehensive goniometric measurements highlighted positions of clinical concern, including cervical spine flexion, scapular protraction, elbow flexion, and wrist ulnar deviation with thumb flexion. Discussion: Findings aligned with prior research suggesting several hr per day of handheld mobile technology use among young adults. Mobile tech posture, as described by goniometric trends, includes several positions of concern for musculoskeletal imbalance or cumulative trauma disorders (e.g., cubital tunnel syndrome; De Quervain's tenosynovitis). Further research is recommended to examine broader societal trends and impact on occupational performance.